2015
DOI: 10.1097/icu.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Eye platelet-rich plasma in the treatment of ocular surface disorders

Abstract: PRP is a portion of the patient's own blood having a platelet concentration above baseline. The main advantage of PRP over other products is the presence of the platelets and associated with this the prolonged release of growth factors that are involved in the wound healing process of the cornea and conjunctival surface. E-PRP seems to be a reliable and effective therapeutic approach to enhance epithelial wound healing and promote ocular surface regeneration in different pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 39 publications
1
66
0
3
Order By: Relevance
“…Improvement of tear film break-up time and Schirmer tear test results have been observed in the study population [Selek et al, 2000]. Human serum and plasma-derived products such as autologous serum eye drops and autologous platelet-rich plasma (PRP) have been demonstrated to be beneficial in PEDs and dry eye disease [Jeng and Dupps, 2009;Hussain et al, 2014;Alio et al, 2015;Tseng et al, 2015;Soni and Jeng, 2016]. Thus, tretinoin maybe the secondary option for the treatment of SM-induced dry eye.…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 94%
See 2 more Smart Citations
“…Improvement of tear film break-up time and Schirmer tear test results have been observed in the study population [Selek et al, 2000]. Human serum and plasma-derived products such as autologous serum eye drops and autologous platelet-rich plasma (PRP) have been demonstrated to be beneficial in PEDs and dry eye disease [Jeng and Dupps, 2009;Hussain et al, 2014;Alio et al, 2015;Tseng et al, 2015;Soni and Jeng, 2016]. Thus, tretinoin maybe the secondary option for the treatment of SM-induced dry eye.…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 94%
“…However, tretinoin did not improve ocular symptoms such as photophobia and foreign body sensation [Selek et al, 2000]. About 50% autologous serum eye drops have been documented to be safe and effective for the management of corneal defects, because the serum composition is similar to the tear, with the presence of epidermal growth factor (EGF) and transforming growth factor-b (TGF-b), leading to regenerative process and healing of corneal defects [Alio et al, 2015;Tseng et al, 2015;Soni and Jeng, 2016]. The efficacy of 0.01% all-transretinoic acid is documented for the treatment of myopia and corneal epithelial erosions [Ubels et al, 1985;Huang et al, 2011].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of platelet-rich plasma (PRP) has become a strategy in the management of several disorders of the ocular surface, including corneal ulcers3 and persistent ocular epithelial defects 4. PRP has an antiapoptotic effect on corneal stromal cells,5 and autologous platelets have been injected for the management of macular holes 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…). Since then, the interest in the use of haematological‐derived substances for topical use as a treatment approach for ocular surface disorders has increased significantly in the last years (Alio & Rodriguez ; Anitua & Muruzabal ), with a great variety of studies reported (Tananuvat & Daniell ; Noble & Loh ; Kojima et al. ; Noda‐Tsuruya & Asano‐Kato ; Alio et al.…”
Section: Introductionmentioning
confidence: 99%